The Rapt of Helen, by Blossius Aemilius Dracontius (Circe de clásicos y modernos, 2018)
In this paper, we offer the translation from latin to spanish, with introduction and short notes, of the eighth of the so-called Carmina Profana or Romulea, written by the poet Blossius Aemilius Dracontius during the 5th Century and transmitted by textual tradition under the title De Raptu Helenae.
Keywords: latin miniature epic; Late Antiquity; Christianism; pagan mythology